Subordinate Mechanism of Legal Regulation of Relations in the Framework of the Contract Procurement System to Meet the Needs of the Public - Evgeny V. Solomonov; Aleksandr A. Yuritsin (Сибирское юридическое обозрение, 2016)
The article discusses the theoretical issues of legal regulation mechanism features of separate stages of public procurement. Conclusions about the legal nature of the type of legal regulation, its relationship with the peculiarities of the legal facts and legal relations are given.